Pancasila Sebagai Pandangan Hidup Bangsa: Analisis Kritis Atas Tantangan Identitas dan Moral di Era Digital - Nur Kholifah; Ikhsan Syaiful; Fadhiela Abhista; M.Sigit; Aulia Melani (Jurnal Hukum dan Sosial Politik, 2025)
The digital era has significantly transformed the way Indonesian society communicates, accesses information, and builds social interactions. These rapid changes have created new challenges for strengthening the values of Pancasila, especially as digital platforms increasingly become spaces where misinformation, hate speech, intolerance, and extreme polarization emerge. This study examines the relevance of Pancasila in guiding ethical behavior within the digital environment and highlights the strategic role of young people as key actors in maintaining national identity and moral integrity. Using a descriptive qualitative approach and literature analysis, the study finds that Pancasila remains highly relevant in addressing technological, social, and cultural disruptions. The values of divinity, humanity, unity, democracy, and social justice are essential for promoting responsible digital citizenship, fostering tolerance, encouraging critical thinking, and strengthening social cohesion. The study concludes that strengthening Pancasila-based digital ethics requires collaboration among the government, educational institutions, digital platforms, and society to ensure that digital transformation aligns with national moral foundations.